Intellectual property law in South East Asia - Antons, Christoph; Blakeney, Michael (Elgar intellectual property and global development series, 2023)
This timely book provides a comprehensive survey of recent developments in intellectual property (IP) law within the Association of Southeast Asian Nations (ASEAN) countries, written by experienced scholars and practitioners in the field. Divided into three insightful parts, the book looks into recent IP developments in individual countries, examining the relationship of ASEAN as a group with the wider region in IP matters, as well as providing comparative studies of copyright infringements, IP in agriculture, IP enforcement and pharmaceutical patenting in the ASEAN countries. Chapters investigate further pressing topics such as IP related to the innovation economy, covering all countries of ASEAN, recently concluded bi- and multilateral agreements and ASEAN IP negotiations with China and other trading partners. Providing regional and international analysis of ASEAN IP law across multiple sectors, this book will prove a valuable resource for IP practitioners, legal academics and law students concerned with Asian IP law and innovation. Students interested in the intersection between IP law, economy and society, from disciplines such as economics, business and political science, will also benefit from this detailed read.